Silver nanowire random network as transparent electrode : physical properties and its application as transparent flexible heater film - Farhan Nur Kholid (2015)
We present comprehensive study of silver nanowire (AgNW) random network on PET as flexible transparent conductive (TC) film. AgNW network sheet resistance dependence on AgNWs size and its area density on film were studied based on percolation theory and the relation between film transmittance on sheet resistance is described, using modification of thin film transmittance equation. AgNW network exhibits outstanding performance as TC film, outperforming graphene layer, SWCNT and CuNW network in terms of its low resistance at high transmittance. Failure of AgNW network due to high current density and contamination due to air contact is presented. AgNW network maximum current density outperforms CuNW network, which AgNW maximum current density was observed to be J_max=50 A/〖cm〗^2. Electrical annealing method is proposed by applying high current near breakdown current for 1 minute periodically, which reduces AgNW sheet resistance by ~18% for network with sheet resistance of R_s~10 Ω/sq . We developed application of AgNW flexible TC film as wearable and transparent flexible heater film fabricated from AgNW ink coated on PET by roll-to-roll processing. AgNW network on PET with sheet resistance of R_s=10.8 Ω/sq with T=70% was used in this work and samples were patterned with non-conductive parallel lines to vary its resistances. Maximum steady-state temperature attained is 92oC at 6 V. Our transparent flexible heater devices also exhibit good performance consistency for small changes in resistance and applied voltage, durability upon multiple usages and bending, capability to defrost in 60s voltage application. Lastly, analytical model was derived based on previous work, which was slightly modified as our experimental techniques employed non-conductive thin lines for high accuracy resistance change. Our AgNW flexible heater film performance agrees with the analytical model and hence we could predict dependence of heater film steady-state temperature on heat conduction coefficient between film bottom surface and material in contact and heater film sheet resistance.